MARKERS OF INFLAMMATION IN PATIENTS WITH ANTIPHOSPHOLIPID SYNDROME AND CARDIOVASCULAR PATHOLOGY - Nataliya Valer'evna Seredavkina; T M Reshetnyak; E N Aleksandrova; A A Novikov; E S Mach; D S Novikova; M A Diatroptova; E L Nasonov; Nataliya Valeryevna Seredavkina; T M Reshetnyak; E N Aleksandrova; A A Novikov; et al. (Научно-практическая ревматология)
Objective: to estimate the levels of high-sensitivity C-reactive protein (hsCRP), interleukin-6 (IL-6), tumor necrosis factor-a (TNF-α), and soluble TNF-α receptor type 1 (sTNF-R1) in patients with antiphospholipid syndrome (APS) and their association with cardiovascular pathology. Subjects and methods. Ninety-six patients, including 52 with primary APS and 44 with systemic lupus erythematosus and APS, were examined. A control group comprised 29 individuals without the signs of autoimmune disease. The levels of hsCRP, IL-6, TNF-α, sTNF-R1, antiphospholipid antibodies, and plasma lipids were studied; ultrasonography measuring the carotid intima-media complex (IMC), electrocardiography (ECG), echocardiography, and Holter ECG monitoring were made. Results. The concentrations of hsCRP, IL-6, TNF-α, and sTNF-R1 were significantly higher in the patient groups than in the controls (p < 0.05). Elevated sTNF-R1 concentrations were more common in angina pectoris than in its absence (OR = 2.13; 95% CI [1.51; 2.99]; p < 0.001). In patients with damage to the valvular apparatus, IL-6, TNF-α, and sTNF-R1 concentrations were significantly higher than those in patients without the defects (p = 0.02, 0.02, and 0.01, respectively). The levels of TNF-α and sTNF-R1 were significantly higher in hypertensive patients than those in non-hypertensives (p = 0.002 and p < 0.001; respectively). The blood concentration of TNF-α was significantly higher in patients having the risk factors and subclinical signs of atherosclerosis that that in those without the signs and risk factors of atherosclerosis (p < 0.05). Analysis showed a direct correlation between the levels of TNF-α, hsCRP, IL-6, and sTNF-R1 and an inverse correlation of those of IL-6 and TNF-α with the duration of posttrombosis (p < 0.05). A correlation was found between the concentrations of TNF-α and sTNF-R1, and IMC of the great arteries, as well as the cumulative coronary risk (p < 0.05). Conclusion. In patients with APS, the levels of all the test markers were significantly higher than those in the controls. An association was revealed between the values of TNF-α and sTNF-R1 and the risk factors and subclinical signs of atherosclerosis.